Developing community-based enterprises from the selected agrarian reform communities in Quezon Province - Miano, Leomar C; Cabrera, Gino A; Yaoc, Claire Ann M; Cayabat, Chona V; Laguador, Aurita A (Asian Journal of Agriculture and Rural Development, 2025)
This research aims to develop community-based enterprises in agrarian reform communities (ARCs) anchored in urban-rural development through climate-resilient agricultural practices in Quezon Province, particularly in the municipalities of Sariaya and Dolores. Following a community-based participatory action research (CBPAR) approach, a needs assessment revealed that local farmers faced significant challenges, including overproduction, low prices, inadequate storage, and limited market access, while a few had ventured into value-added processing. Training gaps in food processing, marketing, and business skills were also identified, highlighting the need for capacity-building programs to enhance entrepreneurship and agricultural productivity. Through participatory learning trials (PLTs), a variety of value-added products, such as tomato ketchup, pork tocino, and buko pie, were developed, incorporating local agricultural produce. Training focused on food processing techniques, entrepreneurial skills, and good manufacturing practices (GMP). While feedback from participants was largely positive, challenges such as high attrition rates in certain training modules were noted. The study recommends the establishment of shared service facilities for food processing, financial assistance for capital development, and the creation of cooperatives to support sustainable entrepreneurship. Additionally, further standardization of products to meet FDA requirements, coupled with continuous monitoring and mentoring, is crucial for ensuring the long-term viability of community-based enterprises.